A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMKN 1 BENAI TALUK KUANTAN REGENCY IN COMPREHENDING RECOUNT TEXTS - Asdiani, Anggun; Ras, Fakhri; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research was aimed at finding out how the ability of the second year students of SMKN 1 Benai in comprehending Recount texts. The sample was 2 Teknik Komputer dan Jaringan (TKJ) 1 (41 students) chosen by cluster random sampling technique. The result showed that the reading ability of the second year students of SMKN 1 Benai in comprehending recount text is in good level with the mean score was 65.60. However, this score was lower than the minimum score criteria is 75.00. The most difficult aspect in comprehending recount text was in finding references is 60.16 which was categorized into mediocre level. Then, the easiest aspect was in finding language features of recount text is 70.73 which was categorized into goo level. Based on research finding, it would be better to recommend as the follow. First, the students need to have more practice in finding references ability in reading activity. Second, the English teacher may increase the students’ motivation and encourage them to read recount text in English book as a part of practicing activities of comprehending recount texts.Key Words: Student’s Ability, Comprehending Recount Texts.